Gender differences in a wide range of trauma symptoms after victimization and accidental traumas: a cross-sectional study in a clinical setting - Erik Ganesh Iyer Søegaard; Zhanna Kan; Rishav Koirala; Edvard Hauff; Suraj Bahadur Thapa (European Journal of Psychotraumatology, 2021)
Background: There are large gender differences in PTSD prevalence. Gender differences in a wide range of trauma symptoms including disturbances in self-organization have not been extensively researched. Objective: To explore gender differences in a wide range of trauma symptoms by comparing victimization trauma (VT) with accidental trauma (AT). Method: A cross-sectional study of 110 traumatized patients attending a mental health outpatient clinic in Oslo, Norway (38.2% men, Mage = 40.4, 40% ethnic Norwegians). The trauma was categorized as VT or AT based on the Life Events Checklist. The Structured Clinical Interview for DSM-IV-PTSD-module and Structured Interview for Disorders of Extreme Stress Not-Otherwise-Specified (DESNOS) assessed a wide range of trauma symptoms. First, we examined gender differences within the trauma categories, then MANCOVA for an adjusted two-by-two between-groups analysis. Results: Among VT patients, men reported more symptoms of alteration of negative self-perception (p = .02, ES = 0.50) and alteration in systems of meaning (p < .01, ES = 1.04). Within the AT group, women reported more symptoms of affect and impulses (p = .01, ES = 0.94). The VT-AT difference was significantly higher in men in intrusion (p < .01, η2 = 0.04), affect and impulses (p < .01, η2 = 0.12), negative self-perception (p < .01, η2 = 0.11), difficulty in relations (p = .01, η2 = 0.10) and alterations in systems of meaning (p = .01, η2 = 0.14). Conclusion: Comparing the VT-AT differences between the genders, men with VT had relatively more symptoms of intrusion, self-organization, identity, ideology/meaning, cognition, and relations difficulties. Effect sizes were moderate to large. Men may be relatively more vulnerable to VT than AT, while women may be more equally affected by VT and AT. Acknowledging possible gender differences in a wider range of trauma symptoms depending on trauma category may have clinical benefits